Nanocochleate: A Novel Drug Delivery System - Y. Pawar, Dr. Ashish (Asian Journal of Pharmaceutics (AJP), 2016)
Nanocochleate is a unique tailor-based system used for microencapsulation and delivery of therapeutics by entrapping them in supramolecular assemblies composed of negatively charged phospholipids and a divalent cation. It is a unique multilayered structure widely used for oral and systemic delivery of wide variety of molecules including genes, vaccines, and antigens. This article highlights the basics of cochleate and nanocochleates, components of nanocochleate drug delivery system, route of administration, dosage form, discovery of nanocochleates, stability of nanocochleate, safety/biocompatibility of the nanocochleate delivery vehicles, advantages of nanocochleates, limitations of nanocochleates, mechanism of action, methods of nanocochleate preparation, and applications of nanocochleate. In a whole nanocochleate represents, a unique novel technology, suitable for oral and systemic delivery of important chemical and biological therapeutics and promises a potential drug delivery system encouraging the future researchers to explore and advance in this new area of drug delivery technology.